Correlation of Bronchoscopy Visualization With Cell Type in Lung Cancer Patients at Haji Adam Malik Hospital Medan 2023 - Fachrina, Intan; Bihar, Syamsul; Syarani, Fajrinur (CoinReads Media Prima, 2024)
Introduction: Lung cancer is defined as a tumor that originates in the lung parenchyma or is located around the bronchi. The two main types are Non Small Cell Lung Carcinoma (NSCLC) and Small Cell Lung Carcinoma (SCLC). When carrying out the procedure, several bronchoscopy visualizations are assessed, such as the bronchial lumen, bronchial mucosa, secretions and bronchial anatomy. Timely bronchoscopic intervention is important for rapid and accurate diagnosis. To determine the relationship between bronchoscopic visualization and carcinoma cell type characteristics from histopathology. Method: This study was conducted with an observational analytic design conducted in a cross-sectional manner, from October 2023 to May 2024. The subjects of this study were taken from the population of lung cancer patients who were hospitalized and outpatient in the hospital, were found to be 67 samples of Non Small Cell Lung Carcinoma (NSCLC). Data included bronchoscopic visualization with lung carcinoma cell type from histopathology, were analyzed univariately and bivariately to assess the relationship between bronchoscopy visualization and lung carcinoma cell type. Results: All patients had Non Small Cell Lung Cancer (100%) are Adenocarcinoma as much as 63% and Squamous Cell Carcinoma as much as 37%. Bronchoscopy visualization shows a central location (62%), partially closed lumen (65%), smooth mucosa (64.5%), mucoid secretion (83.8%), and most often in the right main bronchus (32.2%). Conclusion: There was a significant relationship between bronchoscopy location and type of lung cancer cell (P value 0.001), as well as between mucosa and cell type (P value 0.001).